1982
DOI: 10.1149/1.2123617
|View full text |Cite
|
Sign up to set email alerts
|

A Viscous Flow Model to Explain the Appearance of High Density Thermal SiO2 at Low Oxidation Temperatures

Abstract: Higher density SiO2 results from the thermal oxidation of Si in dry 02 at lower oxidation temperatures. More than 3% higher density is observed for SiO2 grown at 600~ as compared with 1150~ A consistent model for the formation of this material is deduced based on the following: the temperature dependence of the density, the annealing behavior of the higher density SIO2, and on the literature and new measurements of the intrinsic stress in SiO~ films. The model considers viscous flow of a Maxwell solid and hing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
99
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 246 publications
(109 citation statements)
references
References 1 publication
10
99
0
Order By: Relevance
“…This temperature lies precisely within the range where a break occurs in the Arrhenius plots for both k and k , and thus indicates viscous flow may play an important role in the 1 oxidation process. Further studies r vealed thit in addition to the thermal stress an intrinsic stress, on the order of 10 dynes/cm , exists in oxides grown in both wet (56) and dry (56,57) ambients at temperatures below 950*C. The intrinsic stress is a stress component which exists at the oxidizing temperature where the thermal stress component is zero. This intrinsic stress probably arises because the oxide lacks the ability for viscous flow to occur at these temperatures (57), and is not observed at oxidizing temperatures above 975 0 C (56).…”
mentioning
confidence: 98%
“…This temperature lies precisely within the range where a break occurs in the Arrhenius plots for both k and k , and thus indicates viscous flow may play an important role in the 1 oxidation process. Further studies r vealed thit in addition to the thermal stress an intrinsic stress, on the order of 10 dynes/cm , exists in oxides grown in both wet (56) and dry (56,57) ambients at temperatures below 950*C. The intrinsic stress is a stress component which exists at the oxidizing temperature where the thermal stress component is zero. This intrinsic stress probably arises because the oxide lacks the ability for viscous flow to occur at these temperatures (57), and is not observed at oxidizing temperatures above 975 0 C (56).…”
mentioning
confidence: 98%
“…This correction term represents the difference in A for the single-fim (without interface) system of a non-annealed and annealed overlayer with the refractive index calculated from a consideration of stress relaxation". 15 "", 7 ; and represents only a few percent of 5 ,t. The chosen photon energy E=3. 18 eV is in the range of the maximum interface and the minimum overlayer sensitivity.…”
Section: Polarizer Arm Analyzer Ammentioning
confidence: 99%
“…The data in Figure 7 is from Figure 6 at two anneal times, one before and one near saturation, and this plot versus anneal temperature reveals a distinct break in the 900'-970*C range, which corresponds to the viscous flow range, i.e. a temperature above which viscous flow of the oxide is fast 15 . Thus, we consider that the vi.…”
Section: Polarizer Arm Analyzer Ammentioning
confidence: 99%
“…It is observed that a, is larger nearer the Si-SiOe interface where SiOe is produced via the interface reaction between Si and oxidant. The origin of at has been attributed to the partial confinement of the molar volume change accompanying the transformation (5,7,9). Based on the fact that the maximum a, found from extrapolation to zero SiO* thickness is substantially less that the theoretical value of more than 10"1 dynes/cma (7), an initially fast stress relaxation was suggested for the SiOa as it is formed which is followed by a much slower relaxation that is characteristic of the bulk SiOa viscosity (22).…”
Section: Oxidation Kinetics and Viscous Relaxation Effectsmentioning
confidence: 99%
“…A number of studies have reported the observation of film stress as a result of Si oxidation (5)(6)(7)(8)). …”
Section: Introductionmentioning
confidence: 99%